أثر برنامج حاسوبي مقترح لاكتساب مهارات مقرر مستحدثات تكنولوجيا التعليم وتنمية التفكير الابتكاري لدى طلبة قسم تكنولوجيا التعليم- بجامعة إب - اليمن \ - صالح, عيسى محمد علي (Kulliyyah of Education, International Islamic University Malaysia, 2019)
This research investigates the effect of using a proposed software to acquire the new instructional technology skills and develop creative thinking skill among the students of Instructional Technology Department at Ibb University. The impact of this proposed software was investigated in comparison to the conventional teaching methods. To achieve the research objectives, the quasi-experimental research with both experimental and control groups was conducted among 40 second-level students of the Instructional Technology Department at Ibb University. Participants undergo pre and post-test in order to compare the statistical difference before and after implementation of the proposed software. The research instruments used in this study were an observation card to measure the extent to which students have acquired the new instructional technology skills and a test to measure the development of creative thinking skills among students. The results from the observation showed that students in the experimental group are more likely to acquire the new instructional technology skills. The results from paired sample t-test showed statistically significance between the experimental and control group in one creative thinking skill (fluency), however, there was no statistically significant difference in the other two skills of creative thinking (flexibility and originality). These results demonstrated the impact of using the proposed software to acquire the new instructional technology skills compared to the conventional methods. The research recommended programming the specialization courses of the Instructional Technology Department and qualifying students to become instructional technology specialists, using self-learning methods that help them gain better skills and develop creative thinking to employ them to improve and develop the learning process.